Pre‐flowering leaf removal alters grape microbial population and offers good potential for a more sustainable and cost‐effective management of a Pinot Noir vineyard. (17th June 2015) - Sternad Lemut, M.; Sivilotti, P.; Butinar, L.; Laganis, J.; Vrhovsek, U.
Abstract Background and Aims The grapevine canopy microclimate, particularly temperature and relative humidity, is of crucial importance for predisposing grapes to lower or greater incidence of microbial infections. Because of global warming, the widely adopted leaf removal at veraison causes an increase in the temperature of the grape berry surface, leading to sunburn and deterioration of berry composition. Seeking a good alternative, a novel, pre‐flowering leaf removal was studied and compared with post‐flowering approaches using a multidisciplinary approach. Methods and Results The effect of timing of leaf removal on the microbial ecology was studied in a Pinot Noir vineyard during two extremely different vintages. The effectiveness of leaf removal in suppressing Botrytis cinerea was compared with that of fungicide application. Bunch compactness and potential for cost and energy savings were calculated. The results showed that earlier leaf removal offers greater potential for successful control of microbial infections. Pre‐flowering defoliation also led to lower bunch compactness (16–18%) accompanied by a substantial yield reduction (30% in 2010 and 24% in 2011). Conclusions In addition to improved microbial control, the lower yield from pre‐flowering defoliation can eliminate the need for bunch thinning and consequently reduces total energy consumption; thus, the technique can be considered to have good potential for more sustainable and cost‐effective management of the vineyard, saving 27% on costs and as much as 46% on energy. Significance of the Study The sustainability of a novel pre‐flowering defoliation in Pinot Noir was evaluated by studying the microbial ecology of the vineyard and by calculating the potential savings from reduction in spraying and energy.